High Sensitivity C-Reactive Protein Predictive Value for Cardiovascular Disease: A Nested Case Control from Isfahan Cohort Study (ICS) - Koosha, Pooya; Roohafza, Hamidreza; Sarrafzadegan, Nizal; Vakhshoori, Mehrbod; Talaei, Mohammad; Sheikhbahaei, Erfan; Sadeghi, Masoumeh (Global heart, 2020)
High sensitivity C-reactive protein (hs-CRP) was proven to be an independent risk factor for cardiovascular diseases (CVDs). The aim of this study was to investigate the benefits of assessing hs-CRP among individuals with different cardiovascular risk factors. This nested case-control study was obtained from the Isfahan Cohort Study (ICS). Anyone who has been suffering from any CVDs, including myocardial infarction, unstable angina, sudden cardiac death and stroke was put in the case group. Density sampling method was utilized to choose the control group who had no aforementioned CVDs during follow-up. Four quartiles of hs-CRP (Q1: 0.1-2.3, Q2: 2.4-3, Q3: 3.1-4 and Q4: 4.1-14 mg/l) were assessed defining odds ratios (OR) of CVDs prediction in different CVDs risk factor categories. Confidence intervals of 95% are put in brackets. A total of 502 cases and 538 controls were recruited. All hs-CRP quartiles showed increased CVDs likelihood compared to normal subjects in terms of diabetes mellitus (DM) and hypertension (HTN). Second quartile showed a 1.93 [1.33-2.81] and 3.34 [1.36-8.17] increased risks in patients with hypertriglyceridemia or dyslipidemia, respectively. Smokers in the third quartile group revealed increased CVDs risk. The fourth quartile showed significant increased risks in patients suffering from hypercholesterolemia (OR = 1.91 [1.33-2.74]), high LDL-C (OR = 1.88 [1.33-2.66]), and hypertriglyceridemia (OR = 2.31 [1.57-3.41]). Our findings suggested that assessing hs-CRP is beneficial for predicting CVDs in patients with HTN and DM. Furthermore, specific patients with lipid abnormalities or history of smoking benefits from checking hs-CRP.